The power of strategic thinking lock in markets, lock out competitors - Robert, Michel 1941- (McGraw-Hill, 2000)
THE POWER OF STRATEGIC THINKING sums up his original and effective strategy of making anyone's competitors irrelevant: Obsession with your competitors leads to "imitation strategy," the common and disastrous mistake of letting the other side set the rules. Result: The house always wins! Imitators lose. The answer: Learn from major companies like Intel, Wal-Mart, Microsoft, and Goldman Sachs--corporate success stories that Robert explains in fascinating detail--how to develop your own "distinctive strategy" and race ahead of the competition.